2019
DOI: 10.17241/smr.2019.00423
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Slow Wave Sleep Continuity by Mattress with Better Body Pressure Dispersal

Abstract: Background and ObjectiveaaThis study evaluated the effects of a mattress with better body pressure dispersal in comparison to a control mattress on sleep quality. MethodsaaIn this randomized crossover study, 10 healthy young men slept in an experimental sleep room on either a functional mattress made from polyurethane, with a special four-layer three-dimensional structure, or a control mattress made from solid polyester wadding, which is a mattress commercially available in Japan. Polysomnography recordings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The number of short SWS episodes ranging from 0.5-5 min was decreased by body pillow use, although there was no difference in the total duration of SWS between the 2 trials. Differences in the number of short SWS episodes were also observed when the effects of 2 mattress types on sleep were assessed [21]. Although, the mechanism responsible for the suppression of SWS episode fragmentation by body pillow use remains to be elucidated, analysis of the continuity of SWS episodes may provide greater insight into the quality of sleep.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of short SWS episodes ranging from 0.5-5 min was decreased by body pillow use, although there was no difference in the total duration of SWS between the 2 trials. Differences in the number of short SWS episodes were also observed when the effects of 2 mattress types on sleep were assessed [21]. Although, the mechanism responsible for the suppression of SWS episode fragmentation by body pillow use remains to be elucidated, analysis of the continuity of SWS episodes may provide greater insight into the quality of sleep.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely reason for disrupting a lateral sleeping position is excess body pressure distribution on the shoulder and hip [21].…”
Section: Effects Of Body Pillow Use On Sleeping Posture and Sleep Architecture In Healthy Young Adultsmentioning
confidence: 99%
“…It has been demonstrated that insufficient sleep and poor sleep quality are associated with physical, physiological, and psychological impairments [1]. The sleep environment, including sleepwear, bedding, and the mattress, are considered factors conducive to better sleep quality [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%